Determination of Heterocyclic Amines and Acrylamide in Agricultural Products with Liquid Chromatography-Tandem Mass Spectrometry - Lee, Kyung-Jun (Toxicol Res, 2015)
Heterocyclic amines (HCAs) and acrylamide are unintended hazardous substances generated by heating or processing of foods and are known as carcinogenic and mutagenic agents by the animal experiments. A simple method was established for a rapid and accurate determination of 12 types of HCAs (IQ, MeIQ, Glu-P-1, Glu-P-2, MeIQx, Trp-P-1, Trp-P-2, PhIP, AαC, MeAαC, Harman and Norharman) and acrylamide in three food matrices (non-fat liquid, non-fat solid and fat solid) by isotope dilution liquid chromatography-tandem mass spectrometry (LC-MS/MS). In every sample, a mixture of internal standards including IQ-d(3), MeIQx-d(3), PhIP-d(3), Trp-P-2-(13)C(2)-(15)N and MeAαC-d(3) was spiked for quantification of HCAs and (13)C(3)-acrylamide was also spiked for the analysis of acrylamide. HCAs and acrylamide in sample were extracted with acetonitrile and water, respectively, and then two solid-phase extraction cartridges, ChemElut: HLB for HCAs and Accucat: HLB for acrylamide, were used for efficiently removing interferences such as pigment, lipid, polar, nonpolar and ionic compounds. Established method was validated in terms of recovery, accuracy, precision, limit of detection, limit of quantitation, and linearity. This method showed good precision (RSD < 20%), accuracy (71.8~119.1%) and recovery (66.0~118.9%). The detection limits were < 3.1 ng/g for all analytes. The correlation coefficients for all the HCAs and acrylamide were > 0.995, showing excellent linearity. These methods for the detection of HCAs and acrylamide by LC-MS/MS were applied to real samples and were successfully used for quantitative monitoring in the total diet study and this can be applied to risk assessment in various food matrices.